1771. Gut Resistome Changes in Response to Prophylactic Antibiotic Administration During Chemotherapy in Children With Acute Lymphoblastic Leukemia. (26th November 2018) - Margolis, Ellie; Hakim, Hana; Yao, Jiangwei; Rosch, Jason; Tang, Li; Sun, Yilun; Dallas, Ronald; Wolf, Joshua
Abstract: Background: Antibiotic resistance harbored in gut microbiome contributes to the emergence of multi–drug-resistant organisms (MDRO). Pediatric leukemia patients typically receive extensive antibiotics and are at higher risk for infection due to MDRO. Methods: A prospective cohort of children ( n = 242) with acute lymphoblastic leukemia self-collected stool samples at diagnosis and after induction chemothearpy. A third of patients ( n = 69) underwent protocol-driven antibiotic prophylaxis: Levofloxacin (LV) given once neutropenia develops. With neutropenic fever patients on prophylaxis stopped LV and all patients received cefepime. Using metagenomic sequencing, we identified bacterial community composition and after alignment to the Comprehensive Antibiotic Resistance Database were able to determine the presence of bacterial resistance genes in 168 stool samples from 49 patients. Results: Expected changes in the community composition were discovered with LV prophylaxis, including the loss of many Enterobacteriaceae and Enterococcaceae species, offset by increases in Bacteroides species. Unexpectedly, LV prophylaxis reduced the acquisition of VanA cluster of vancomycin resistance genes and did not increase acquisition of β-lactamase or fluoroquinolone (FQ) resistance gene families. Conclusion: LV prophylaxis during leukemia treatment imparts predictable changes in gut bacterial communities but counter intuitively decreases antibiotic resistance in the gut microbiome reservoir. The reduction in VanA cluster of genes is likely due to depletion of Enterococcaceae species via direct killing or loss of synergistic partners. The lack of increase in target (FQ) or off-target resistance suggests that prophylaxis altered community selective pressures or prophylaxis drug concentrations were sufficient to limit the outgrowth of resistant mutants. Disclosures: J. Wolf, Karius Inc.: Investigator, Research support.